2010
DOI: 10.2337/dc09-2176
|View full text |Cite
|
Sign up to set email alerts
|

Day-to-Day Variation of Insulin Requirements of Patients With Type 2 Diabetes and End-Stage Renal Disease Undergoing Maintenance Hemodialysis

Abstract: OBJECTIVETo evaluate day-to-day variations of insulin needs in type 2 diabetic patients with end-stage renal disease (ESRD) on maintenance hemodialysis.RESEARCH DESIGN AND METHODSWe developed a 24-h euglycemic clamp in patients who received an average of 2,200 calories in a standardized three-meal and two-snack regimen per day, adjusted to body size and sex. Intravenous insulin was adjusted every 30 min to achieve 5.5 ± 1.1 mmol/l glycemia over 24 h prehemodialysis, during hemodialysis session, and 24 h posthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 17 publications
1
35
0
5
Order By: Relevance
“…14 Clinical studies are in agreement with the concept that uremic toxins are involved in insulin resistance in uremia. In a group of type 2 diabetic patients on maintenance hemodialysis, Sobngwi et al 15 demonstrated a 15% decrease in the daily insulin needs in the day after hemodialysis compared with the insulin needs before hemodialysis, with a significant reduction of basal hourly insulin requirement by 25%, in the face of unchanged bolus, and unchanged body-weight-indexed total insulin dose. This study confirmed earlier findings of DeFronzo et al 16 that 10 weeks of thrice-weekly hemodialysis improves insulin sensitivity in uremic patients.…”
Section: Insulin Resistance In Uremiamentioning
confidence: 97%
“…14 Clinical studies are in agreement with the concept that uremic toxins are involved in insulin resistance in uremia. In a group of type 2 diabetic patients on maintenance hemodialysis, Sobngwi et al 15 demonstrated a 15% decrease in the daily insulin needs in the day after hemodialysis compared with the insulin needs before hemodialysis, with a significant reduction of basal hourly insulin requirement by 25%, in the face of unchanged bolus, and unchanged body-weight-indexed total insulin dose. This study confirmed earlier findings of DeFronzo et al 16 that 10 weeks of thrice-weekly hemodialysis improves insulin sensitivity in uremic patients.…”
Section: Insulin Resistance In Uremiamentioning
confidence: 97%
“…A recently published small study of patients on outpatient maintenance hemodialysis showed both pre-and post-hemodialysis variation in patient insulin requirements, as well as diurnal variation in insulin requirements. 16 The study authors found that the dose of basal insulin should be decreased by 25% on the day following hemodialysis, while nutritional bolus doses can remain unchanged. 16 In addition to adjustments in insulin dosing pre-and post-hemodialysis, patients must have close monitoring of point-of-care BG levels.…”
Section: Hemodialysis and Glycemic Controlmentioning
confidence: 97%
“…16 The study authors found that the dose of basal insulin should be decreased by 25% on the day following hemodialysis, while nutritional bolus doses can remain unchanged. 16 In addition to adjustments in insulin dosing pre-and post-hemodialysis, patients must have close monitoring of point-of-care BG levels.…”
Section: Hemodialysis and Glycemic Controlmentioning
confidence: 97%
“…In addition, the act of dialysis further alters insulin requirements. Using a 24-h euglycaemic clamp in patients with T2D on HD, there is evidence that there is a significant reduction (15%) in basal insulin requirements the day following an HD session 68. Changing the mode of dialysis (eg, from CAPD to APD) requires adjustments to the insulin regime to limit extremes of glycaemia 56…”
Section: Treatment Options For Diabetic Patients On Dialysismentioning
confidence: 99%